Long-term PM0.1 exposure and human blood lipid metabolism: New insight from the 33-community study in China. (15th June 2022) - Zhang, Wangjian; Gao, Meng; Xiao, Xiang; Xu, Shu-Li; Lin, Shao; Wu, Qi-Zhen; Chen, Gong-Bo; Yang, Bo-Yi; Hu, Li-Wen; Zeng, Xiao-Wen; Hao, Yuantao; Dong, Guang-Hui
Abstract: Ambient particles with aerodynamic diameter <0.1 μm (PM0.1 ) have been suggested to have significant health impact. However, studies on the association between long-term PM0.1 exposure and human blood lipid metabolism are still limited. This study was aimed to evaluate such association based on multiple lipid biomarkers and dyslipidemia indicators. We matched the 2006–2009 average PM0.1 concentration simulated using the neural-network model following the WRF-Chem model with the clinical and questionnaire data of 15, 477 adults randomly recruited from 33 communities in Northeast China in 2009. After controlling for social demographic and behavior confounders, we assessed the association of PM0.1 concentration with multiple lipid biomarkers and dyslipidemia indicators using generalized linear mixed-effect models. Effect modification by various social demographic and behavior factors was examined. We found that each interquartile range increase in PM0.1 concentration was associated with a 5.75 (95% Confidence interval, 3.24–8.25) mg/dl and a 6.05 (2.85–9.25) mg/dl increase in the serum level of total cholesterol and LDL-C, respectively. This increment was also associated with an odds ratio of 1.25 (1.10–1.42) for overall dyslipidemias, 1.41 (1.16, 1.73) for hypercholesterolemia, and 1.90 (1.39, 2.61) for hyperbetalipoproteinemia. Additionally, we found generally greater effect estimates among the younger participants and those with lower income or with certain behaviors such as high-fat diet. The deleterious effect of long-term PM0.1 exposure on lipid metabolism may make it an important toxic chemical to be targeted by future preventive strategies. Graphical abstract: Image 1 Highlights: PM0.1 concentration was associated with increased level of total cholesterol and LDL-C. Long-term PM0.1 exposure was related to multiple indicators of dyslipidemia status. Age and income modified the association between PM0.1 concentration and outcomes. Younger subjects and those with lower income or high-fat diet were more vulnerable.